Voice Quality in Laryngotracheal Stenosis: Impact of Dilation and Level of Stenosis. (May 2015) - Hillel, Alexander T.; Karatayli-Ozgursoy, Selmin; Benke, James R.; Best, Simon; Pacheco-Lopez, Paulette; Teets, Kristine; Starmer, Heather; Akst, Lee M.
Objective: To assess the impact of suspension microlaryngoscopy with balloon dilation on voice-related quality of life (V-RQOL) in laryngotracheal stenosis (LTS). Methods: Retrospective chart review of LTS patients dilated at a tertiary-care academic hospital from 2010 to 2013. Data were obtained and then analyzed. LTS was stratified by (1) subglottic or tracheal stenosis and (2) multilevel stenosis (MLS; glottic and subglottic/tracheal). Pre- and postoperative V-RQOL and grade, roughness, breathiness, asthenia, strain (GRBAS) scores were compared. The number and frequency of balloon dilation procedures over the lifetime were secondary outcome variables. Results: Thirty-eight patients were identified: 26 subglottic/tracheal and 12 multilevel. Of these, 71.4% required multiple dilations, with greatest dilations/patient for multilevel stenosis (4.8). V-RQOL improved in the 27 patients with completed pre- and postoperative scores from a mean of 70.4 to 80 ( P = .025). Pre/postoperative V-RQOLs for tracheal/subglottic (mean, 82.8/93.8) were significantly higher ( P = .0001/.0001) than multilevel stenosis (48/55.3). Voice quality-of-life improvement was significant for the subglottic/tracheal cohort ( P = .036) but not for the MLS group. GRBAS was performed pre- and postoperatively in 10 patients with improvement in all domains except breathiness. Conclusion: Laryngotracheal stenosis is associated with dysphonia. Patients with glottic involvement have significantly worse voice quality of life than those with tracheal/subglottic stenosis. Endoscopic balloon dilation improves V-RQOL in patients with subglottic/tracheal stenosis.